KARAKTER TOKOH UTAMA DALAM NOVEL GIBRAN DIRGANTARA KARYA FALISTIYANA - Zelin Monica Monica; Jelita Zakaria; Loliek Kania Atmaja; Man Hakim; Ira Yuniati (Jurnal Membaca (Bahasa dan Sastra Indonesia), 2026)
The problem in this study is how the main character in Falistiyana's novel Gibran Dirgantara is portrayed. The purpose of this study is to describe how the main character in Falistiyana's novel Gibran Dirgantara is portrayed. In this novel, the main character, Gibran Dirgantara, is a high school teenager who exhibits a complex character and shows significant character development throughout the story. The method used in this study is qualitative descriptive, with content analysis as the data analysis technique. The content referred to in this study is the main character's character as depicted in the quotations in Falistiyana's novel Gibran Dirgantara. Research data was obtained by reading the novel, marking or underlining each sentence, collecting the underlined parts of the novel, and clarifying the data into a detailed table of the text and analyzing it based on four types of character according to Gunawan's theory, namely sanguine, melancholic, choleric, and phlegmatic. The research findings show that Gibran's most dominant character is choleric, with a total score of.